Stop System

The aircraft suspension system with a concrete base and polyurethane/polyurea layers addresses vulnerabilities in existing systems by enhancing energy absorption and durability against environmental factors, ensuring effective deceleration of transportation equipment.

JP7623088B2Active Publication Date: 2025-01-28RUNWAY SAFE IPR AB
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2022512366
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-18
Filing Date
2020-08-21
Publication Date
2025-01-28
Estimated Expiration
2040-08-21

AI Technical Summary

Technical Problem

Existing aircraft suspension systems are vulnerable to environmental conditions such as weather changes and jet blast, leading to system degradation and potential destruction, and they lack sufficient resistance to aircraft impacts.

Method used

A suspension system comprising a concrete base covered by polyurethane and polyurea layers, which are applied using specific compositions and methods to enhance energy absorption and durability.

Benefits of technology

The system provides excellent energy absorption characteristics and resistance to environmental factors, ensuring effective deceleration of transportation equipment under various conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623088000001
    Figure 0007623088000001
  • Figure 0007623088000002
    Figure 0007623088000002
  • Figure 0007623088000003
    Figure 0007623088000003
Patent Text Reader

Abstract

An energy absorption system (1) for stopping a transport device, comprising a concrete base (2) located on a friable support (3) and covered by at least one polyurethane layer (4) and at least one polyurea layer (5), and a method for manufacturing the energy absorption system.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of transportation arrestment systems and methods of manufacture thereof. [Background technology]

[0002] Runway end aircraft arrestment systems are becoming more commonplace to catch aircraft when they overshoot the runway due to speed or weather conditions. When such an event occurs at the end of a runway, a bed of specially engineered material may be laid down to minimize or avoid the severity of the impact to people and aircraft. Such specially engineered materials are typically highly energy absorbing materials that collapse under the weight of the aircraft. The aircraft is slowed down due to the loss of energy required to crush the specially engineered material. Current systems typically use cellular cement materials or lightweight aggregate foams made from recycled glass. Summary of the Invention

[0003] Periodically changing severe weather conditions (e.g., summer sunshine and winter near freezing temperatures, rain, hail, etc.) can affect current aircraft arresting systems, causing them to become ineffective over time. Additionally, light traffic and constant jet blast from departing aircraft can lead to the destruction of currently known arresting systems. In particular, the surfaces of current systems do not exhibit sufficient resistance to such environmental and aircraft-induced conditions.

[0004] The object of the present invention is to overcome the drawbacks of the stopping systems known in the art and to provide a transportation stopping system which can be rapidly manufactured in an environmentally friendly manner and at limited cost.

[0005] The present invention relates to an energy absorbing system for arresting a transport device, comprising a concrete base resting on a friable support and covered with at least one polyurethane layer and at least one polyurea layer.

[0006] Surprisingly, it has been found that energy absorbing systems including the above structures exhibit superior stopping characteristics compared to other energy absorbing systems known in the art. In particular, the use of polyurethane and polyurea layers in combination with a concrete base on a friable support provides a superior energy absorbing system.

[0007] Another aspect of the invention is a method of manufacturing an energy absorption system for shutting down a transportation device, comprising the steps of: a) applying concrete onto a friable support to form a concrete base; b) applying a first composition comprising at least one polyol, at least one catalyst, and at least one isocyanate onto the concrete base to form a polyurethane layer; c) applying onto said polyurethane layer a second composition comprising at least one polyamine, and at least one isocyanate to form a polyurea layer.

[0008] To produce the above-mentioned energy absorbing system for immobilizing a vehicle, a layer of concrete, a layer of polyurethane, a layer of polyurea are applied over a friable substrate, which is deposited substantially flat in areas adjacent to or at the edges of runways or roads and streets.

[0009] A further aspect of the invention relates to an aircraft runway comprising at least one energy absorbing system for stopping a transport device according to the invention.

[0010] Another aspect of the invention relates to a road or street comprising at least one energy absorption system for stopping a transport device according to the invention. [Brief description of the drawings]

[0011] [Figure 1] 1 shows a cross-sectional view of an energy absorbing system 1 for arresting a transport device according to the present invention. The system comprises a concrete base 2 arranged on a friable support 3. At least one polyurethane layer 4 covers the base 2, whereby a polyurea layer 5 and an anti-slip layer 6 further cover the polyurethane layer 4.

[0012] [Diagram 2] FIG. 2 shows an energy absorbing system for stopping a transport device depicted in FIG.

[0013] [Diagram 3] 3 shows a grid structure of an energy absorption system 1 for stopping a transport device. The grid structure comprises a first grid 8 of cuts and a second grid 9 of cuts.

[0014] [Figure 4] 4 shows a cross-section of an energy absorbing system 1 for stopping a transport device according to the present invention having a cut-out 10. The cut-out 10 may be provided with a joint profile 11 arranged therein.

[0015] [Diagram 5] 5 shows a cross-section of an energy absorbing system 1 for stopping a transport device according to the invention, which comprises a notch 12. The notch 12 may comprise a joint profile 13 arranged therein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The method of the invention makes it possible to manufacture an energy absorbing system for arresting any kind of transport vehicle. In a first step, concrete is applied onto a friable support to form a concrete base. The friable support itself is usually manufactured on the terrain, preferably a substantially flat terrain, on which the entire system should be effective.

[0017] In a second step of the method of the present invention, at least one polyurethane layer is applied onto a concrete base by mixing at least one isocyanate with a first composition comprising at least one polyol and at least one catalyst either directly prior to application to the base or directly on the concrete base.

[0018] After formation of the polyurethane layer in step b., at least one polyurea is formed on said polyurethane layer by applying a second composition (second mixture) comprising an isocyanate and at least one polyamine.

[0019] The superior properties of the energy absorbing system of the present invention are a result of the combination of various layers including the friable substrate, concrete, polyurethane and polyurea.

[0020] The energy absorption system of the present invention can be used to stop various types of vehicles. As used herein, the term "vehicle" refers to automobiles, trucks, aircraft, etc. Thus, the system of the present invention can be used to stop vehicles such as automobiles, trucks, and aircraft.

[0021] As used herein, the terms "at least one isocyanate," "at least one polyol," "at least one polyamine," and "at least one catalyst" respectively mean that one or more different types of isocyanates, one or more different types of polyols, one or more different types of polyamines, and one or more different types of catalysts can be used in the process of the present invention.

[0022] The at least one isocyanate and the various compositions can be applied (sprayed) onto the surface using a brush, roller, spray or any other suitable application technique, whereby application using a spray is most preferred. Additionally, application of the concrete to the friable substrate can be done by spraying or using any other known technique commonly used for application of concrete to a surface.

[0023] According to a preferred embodiment of the present invention, after step a, in step a1, a leveling composition is applied (spread) onto the concrete base to form a leveling layer.

[0024] Application of the leveling composition to the concrete base is useful for closing the pores of the concrete base and providing better bonding of the polyurea layer.

[0025] According to a preferred embodiment of the present invention, a third composition (third mixture) comprising at least one isocyanate and at least one polyol is applied onto the concrete base after step a. or after step a1., and optionally onto the polyurethane layer after step b., wherein the third composition is substantially free of water.

[0026] The at least one isocyanate and the third composition (the "primer system") are designed to eliminate any pinholes in the subsequent layers of the system and to seal the concrete surface against water penetration. Additionally, the aforementioned combination of the at least one isocyanate and the third composition can also be applied over the polyurethane layer, resulting in better bonding between these layers.

[0027] According to another preferred embodiment of the present invention, a fourth composition (fourth mixture) comprising at least one isocyanate, at least one polyamine and at least one defoamer (air release agent, air remover) is applied onto the polyurea layer to obtain an anti-slip layer.

[0028] Providing a polyurea layer over (on top of) the stopping system is advantageous with respect to color stability and the ability to incorporate fine aggregate for anti-skid properties.

[0029] According to a preferred embodiment of the present invention, the concrete has a strength of 200 N / mm 2 Less than 150N / mm 2 Less than 100N / mm 2 This includes limestone (limestone) having a maximum compressive strength of less than 10 ...

[0030] Maximum compressive strength is 200N / mm 2 Being less than 1000 mm is advantageous because it allows the concrete to break down under pressure from transportation equipment such as airplanes, trucks and buses.

[0031] According to a further preferred embodiment of the present invention, the concrete contains limestone having an average particle size of 0.01 to 20 mm, preferably 0.02 to 15 mm, more preferably 0.05 to 10 mm, and even more preferably 0.1 to 8 mm.

[0032] The limestone present in the concrete base preferably has an average grain size of less than 20 mm. This size limit is advantageous in terms of fracture of the base when pressure is applied.

[0033] According to a further preferred embodiment of the invention the concrete is substantially free of quartz.

[0034] Surprisingly, it has been found that using concrete that is substantially free of quartz exhibits better results in terms of fracture properties under pressure. Furthermore, quartz / sand can have a negative impact on the environment in terms of particle contamination and dust that can be harmful to breathing.

[0035] As used herein, the term "substantially free" means that the concrete contains less than 5% by weight quartz, preferably less than 2% by weight, and more preferably less than 1% by weight quartz.

[0036] According to another further preferred embodiment of the invention, the concrete comprises cement, which is a common binder in concrete and is preferably used to manufacture concrete bases.

[0037] The concrete is applied onto the support in a thickness of 10-400 mm, preferably 15-300 mm, more preferably 20-200 mm, more preferably 10-100 mm, more preferably 15-80 mm, more preferably 20-60 mm.

[0038] It has been found that a thickness of the concrete base of less than 400 mm, preferably less than 60 mm, has a positive effect on the failure of the concrete base under pressure.

[0039] According to a further preferred embodiment of the present invention, the friable support comprises rocks and / or foam glass having an average particle size (grain size) of 1-10 cm, preferably 2-8 cm, more preferably 3-6 cm, even more preferably 4-5 cm.

[0040] The use of such a frangible support is particularly advantageous because the frangible support contributes to the absorption of kinetic energy from the vehicle.

[0041] The foam glass used in the system of the present invention may be made from inorganic non-metallic glass materials. Due to the foam structure, the foam glass contains a large number of bubble structures (foam structures) having a diameter in the range of 0.1 to 5 mm, preferably 0.2 to 4 mm, more preferably 0.5 to 3 mm, more preferably 1 to 2 mm. The foam glass of the present invention may contain open cell and / or closed cell bubbles. Methods for producing such foam glass are well known in the art.

[0042] According to another preferred embodiment of the invention, the at least one polyol of the first composition is selected from the group consisting of polyester polyols, preferably polyethylene terephthalate (PET) based polyols, more preferably recycled PET based polyols.

[0043] The polyester polyol is preferably selected from the group consisting of Mannich-based polyols, aliphatic amine-based polyols, and polyether-based polyols.

[0044] According to a preferred embodiment of the invention, the at least one catalyst of the first composition is selected from the group consisting of 1,3,5-tris(dimethylaminopropyl)-1,3,5-hexahydrotriazine, N,N,N'-trimethyl-N'-hydroxyethyl-bisaminoethyl ether and potassium octoate (potassium caprylate).

[0045] According to a further preferred embodiment of the present invention, the first composition comprises 60 to 95% by weight, preferably 70 to 90% by weight, of at least one polyol and 1 to 5% by weight, preferably 2 to 4% by weight, of at least one catalyst.

[0046] According to another preferred embodiment of the invention, the first composition comprises 1 to 3% by weight, preferably 1.2 to 2% by weight, of a surfactant, preferably a silicone surfactant.

[0047] A surfactant is preferably used to aid in the development (growth) of a consistent closed cell structure in the first composition, which is preferably applied or prepared as a foam.

[0048] The surfactant is preferably selected from the group consisting of silicone-based surfactants and organic non-ionic surfactants.

[0049] It is preferred to apply the polyurethane in the form of a foam. To create the foam, it is necessary to generate a gas simultaneously with the occurrence of urethane polymerization. The gas may be carbon dioxide generated by reacting an isocyanate with water or added as a gas. According to the invention, it is preferred to add water.

[0050] Therefore, according to a preferred embodiment of the present invention, the first composition contains 1 to 5% by weight, preferably 1.2 to 3% by weight, more preferably 1.5 to 2% by weight of water.

[0051] According to another preferred embodiment of the present invention, the first composition comprises 5-20% by weight of a flame retardant, preferably 10-20% by weight, more preferably 11-15% by weight.

[0052] In order to render the energy absorbing system of the present invention heat resistant, the first composition of the present invention may include a flame retardant.

[0053] The flame retardant is preferably selected from the group consisting of tris(chloropropyl)phosphate, aluminum trihydrate, antimony oxide and sodium borate.

[0054] According to a further preferred embodiment of the present invention, the at least one isocyanate and the first composition are mixed during step b. in a ratio of 0.1:1 to 5:1, preferably 0.5:1 to 4:1, more preferably 0.8:1 to 2.5:1, even more preferably 0.9:1 to 1.1:1.

[0055] According to another preferred embodiment of the present invention, at least one isocyanate and the first composition are applied (sprayed) onto a concrete base to obtain a polyurethane layer with a thickness of 1 to 50 mm, preferably 1 to 40 mm, more preferably 1 to 30 mm, even more preferably 1 to 20 mm, more preferably 1 to 15 mm, more preferably 5 to 10 mm.

[0056] It has been found that having a polyurethane layer thickness within these ranges is advantageous with respect to fracture.

[0057] The polyamine of the second composition is preferably selected from the group consisting of polyoxypropylene diamine, diethyltoluene diamine, methylene dianiline, polyoxypropylene triamine, substituted methylene dianiline and secondary methylene dianiline.

[0058] According to a preferred embodiment of the invention, the second composition comprises 60 to 100% by weight, preferably 65 to 95% by weight, more preferably 65 to 90% by weight of at least one polyamine.

[0059] According to another preferred embodiment of the invention, the second composition comprises 2-20% by weight, preferably 5-15% by weight, more preferably 5-10% by weight of a flame retardant.

[0060] To render the top layer of the energy absorbing system of the present invention flame retardant, the second composition includes at least one flame retardant.

[0061] The flame retardant is selected from the group consisting of tris(chloropropyl) phosphate, aluminum trihydrate, antimony oxide, and sodium borate.

[0062] According to a preferred embodiment of the present invention, the at least one isocyanate and the second composition are mixed during step c. in a ratio of 0.5:1.5 to 1.5:0.5, preferably 1:1.

[0063] According to another preferred embodiment of the present invention, at least one isocyanate and the second composition are applied onto the polyurethane layer to obtain a polyurea layer with a thickness of 0.1 to 10 mm, preferably 0.2 to 5 mm, more preferably 0.5 to 3 mm, even more preferably 0.5 to 2 mm, more preferably 0.5 to 1.2 mm, and even more preferably 0.5 to 1 mm.

[0064] According to a preferred embodiment of the present invention, at least one polyol of the third composition is a hydroxyl-containing triglyceride or fatty acid, preferably selected from the group consisting of castor oil, licoric acid, cashew nut oil and soy-based polyols.

[0065] The use of naturally occurring fatty acids makes the process of the present invention more environmentally friendly compared to other processes known in the art that use synthetic hydroxyl group donors.

[0066] According to another preferred embodiment of the invention, the at least one isocyanate and the at least one polyol of the third composition are applied onto the concrete base and / or optionally onto the polyurethane layer in a ratio of 0.5:1.5 to 1.5:0.5, preferably 1:1.

[0067] According to a preferred embodiment of the invention, the at least one polyamine of the fourth composition is selected from the group consisting of polyaspartic acid esters, preferably polyaspartic acid esters based on methylenedicyclohexylamine.

[0068] According to another preferred embodiment of the invention, the at least one defoaming agent of the fourth composition is selected from the group consisting of silicone-based release agents, preferably methylated silica and / or dimethyl silicone polymers.

[0069] The fourth composition preferably comprises from 80% to 98% by weight, preferably from 90% to 98% by weight, more preferably from 95% to 98% by weight of at least one polyamine.

[0070] According to a preferred embodiment of the invention, the fourth composition comprises from 2% to 5% by weight, preferably from 2% to 4% by weight, of at least one defoaming agent.

[0071] Defoaming agents aid in producing polyurea foams. The preferred defoaming agent used is water.

[0072] According to a preferred embodiment of the present invention, the at least one isocyanate and the fourth composition are applied onto the polyurea layer (4) in a ratio of 0.5:2 to 2:0.5, preferably 1:1.5.

[0073] The at least one isocyanate and the fourth composition are applied onto the polyurea layer (4) in a thickness of 0.1 to 2 mm, preferably 0.25 to 1 mm.

[0074] According to a preferred embodiment of the present invention, the at least one isocyanate is selected from the group of isocyanates consisting of aliphatic isocyanates, aromatic isocyanates, aliphatic / aromatic diisocyanates, and mixtures thereof. The aliphatic isocyanates are selected from the group consisting of methylene diisocyanate, difunctional monomers of tetraalkylxylene diisocyanate, cyclohexane diisocyanate, 1,12-dodecane diisocyanate, 1,4-tetramethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate. The aromatic isocyanate is selected from the group consisting of m-phenylene diisocyanate, p-phenylene diisocyanate, polymethylene polyphenylisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, dianisidine diisocyanate, bitolylene diisocyanate, naphthalene-1,4-diisocyanate and diphenylene-4,4'-diisocyanate. The aliphatic / aromatic diisocyanate is selected from the group consisting of xylylene-1,3-diisocyanate, bis(4-isocyanatophenyl)methane, bis(3-methyl-4-isocyanatophenyl)methane and 4,4'-diphenyl-propane diisocyanate.

[0075] According to a preferred embodiment of the present invention, the at least one isocyanate in step c. is an aromatic isocyanate.

[0076] Aromatic isocyanates have been found to be advantageous for forming substantially hard (rigid) spray foams, as aliphatic isocyanates are too slow in reacting to produce foam systems for this purpose.

[0077] According to a preferred embodiment of the present invention, the leveling composition comprises at least one isocyanate, preferably as defined above, at least one polyamine, preferably as defined above, and / or at least one polyol, preferably as defined above.

[0078] In a further preferred embodiment of the present invention, the leveling composition comprises a mixture of a polyol and a polyamine.

[0079] According to another preferred embodiment of the present invention, the leveling composition comprises quartz particles.

[0080] The quartz particles have an average size of 0.05 to 1 mm, preferably 0.05 to 0.75 mm, more preferably 0.05 to 0.5 mm, and even more preferably 0.1 to 0.5 mm.

[0081] According to another preferred embodiment of the present invention, the leveling composition further comprises a floating agent, preferably pyrogenic silica, also known as fumed silica. The pyrogenic silica may have an average particle size of 5 to 50 nm. The particles are typically non-porous and have an average particle size of 50 to 600 nm. 2 The density is preferably 160 to 190 kg / m 3 It is.

[0082] It is particularly advantageous if the pyrogenic silica is treated with polydimethylsiloxane (PDMS). Such treatment makes the surface of the pyrogenic silica particles more hydrophobic. Alternatively, the pyrogenic silica may be treated with polydimethylsiloxane.

[0083] According to a preferred embodiment of the present invention, the leveling composition comprises a mixture of at least one polyol and at least one polyamine in a ratio of 2:1 to 6:1, preferably 3:1 to 5:1, more preferably 3.5:1 to 4.5:1.

[0084] The mixture of polyols and polyamines in the leveling composition is particularly advantageous since it allows one to obtain a composition that exhibits good rheological properties when the composition is applied to a concrete surface to give a smooth and even surface.

[0085] According to a further preferred embodiment of the present invention, the levelling composition comprises at least one isocyanate and at least one polyamine and / or at least one polyol in a ratio of 3:1 to 7:1, preferably 4:1 to 6:1, more preferably 4.5:1 to 5.5:1.

[0086] According to a preferred embodiment of the present invention, the leveling composition comprises at least one isocyanate and quartz particles in a ratio of 3:1 to 1:1, preferably 2.5:1 to 1.5:1, more preferably 2:1 to 1.5:1, and even more preferably 1.8:1 to 1.7:1.

[0087] According to a further preferred embodiment of the present invention, the leveling composition contains 0.5 to 1.2 wt %, preferably 0.6 to 1 wt %, more preferably 0.7 to 0.9 wt %, and even more preferably 0.8 to 0.9 wt % of a floating agent.

[0088] According to another preferred embodiment of the present invention, the leveling layer 7 may have a thickness of 0.1 to 10 mm, preferably 0.5 to 5 mm, more preferably 1 to 4 mm, and even more preferably 1 to 3 mm.

[0089] According to a preferred embodiment of the method according to the invention, a first grid 8 of incisions 10 is formed in the concrete base 2. The incisions 10 of the first grid 8 start on the surface of the concrete base 2 facing away from the friable support 3, extend towards the friable support 3 and preferably have a depth smaller than the thickness of the concrete base 2.

[0090] The method according to the invention preferably comprises the step of forming a second grid 9 of incisions 12. The incisions 12 of the second grid 9 originate on the surface of the polyurea layer 5 opposite the polyurethane layer 4 and extend through the polyurea layer 5, the polyurethane layer 4 and the concrete base 2 to the friable support 3.

[0091] The cuts 10 in the first grid 8 act as contraction joints and the cuts 12 in the second grid 9 act as expansion joints. Cracks in the structure of the energy absorption system can cause an increasingly rapid deterioration of the system, especially when exposed to rain and / or snow, due to chemical reactions that can occur inside the concrete, or due to ice formation in these cracks in winter, subjecting the cracked system according to the invention to additional mechanical stresses.

[0092] Due to the thermal stresses exhibited by the energy absorption system according to the invention, for example when exposed to sunlight or other heat sources or thermal radiation, on the other hand when exposed to low temperatures in winter or cold climates, a gradual deterioration of the structural bonds (structural condensation) and the formation of cracks in the energy absorption system is likely to occur. By including the first grid 8 of cuts 10 acting as shrinkage joints, the thermal stresses caused by the expansion of the concrete base 2 are mitigated and the formation of such thermally induced cracks or structural defects is inhibited. The cuts 10 of the first grid 8 preferably have a depth less than the thickness of the concrete base 2. This design compensates for the temperature gradient in the concrete base 2 which increases the expansion of the concrete base 2 close to the surface of the energy absorption system which is often directly exposed to heat and thermal radiation.

[0093] The incisions 12 in the second grid 9 act as expansion joints and relieve thermal stresses caused by the contraction of the energy absorbing system when exposed to low temperatures. Under low temperature conditions, the energy absorbing system contracts in an essentially uniform manner throughout its thickness. Thus, the incisions 12 in the second grid 9 extend through the polyurea layer 5, the polyurethane layer 4 and the concrete layer 2 to the friable support 3.

[0094] According to a preferred embodiment, the second grid 9 has a larger mesh size than the first grid 8. The mesh size of the second grid 9 can be made larger than that of the first grid 8, since the expansion joints can also act as contraction joints.

[0095] Optionally, in the method according to the invention joint profiles 11, 13 are introduced into at least some of the incisions 10 of the first grid 8 and / or into at least some of the incisions 12 of the second grid 9. The joint profiles 11, 13 prevent material from accumulating in the incisions 10, 12 during the manufacture of the energy absorption system and obstructing the incisions 10, 12. In particular, the joint profile 11 used in the first grid 8 has a profile head, which extends beyond the width of the incisions 10 of the first grid 8.

[0096] The joint profiles 11, 13 preferably comprise or consist exclusively of ethylene propylene diene monomer (EPDM) rubber.

[0097] Another aspect of the invention relates to an energy absorption system for stopping a transport vehicle, obtainable by the method according to the invention.

[0098] A further aspect of the invention relates to an energy absorbing system for stopping transport equipment, comprising a concrete base 2 placed on a friable support 3 and covered by at least one polyurethane layer 4 and at least one polyurea layer (5).

[0099] Surprisingly, it has been found that a system comprising the above-described layers on a friable substrate exhibits superior energy absorption properties to other energy absorption systems known in the art. The interaction between the polyurethane layer and the polyurea layer on the friable substrate has been found to be advantageous.

[0100] According to a preferred embodiment of the invention, the at least one polyurethane layer 4 is covered with at least one polyurea layer 5 .

[0101] It is particularly advantageous if at least one polyurethane layer of the energy absorbing system of the invention is covered with at least one polyurea layer, this sequence of the two layers in particular providing an energy absorbing system that is resistant with respect to environmental influences and is suitable for use in heavy transport equipment such as aircraft.

[0102] According to a preferred embodiment of the present invention, the concrete base and the layer covering said base are substantially jointless.

[0103] The method of the invention makes it possible to obtain an energy absorbing system for arresting a transport device, the surface of which is substantially jointless.

[0104] The polyurea layer 5 is preferably covered with an anti-slip layer comprising polyurea.

[0105] The energy absorbing system of the present invention can be used at the edge of an aircraft runway or a flat road. To allow people or light transport to move on such a system, at least one polyurea layer is preferably covered with an anti-slip layer. The anti-slip layer may also include polyurea.

[0106] A further aspect of the invention relates to an aircraft runway comprising at least one energy absorbing system for stopping a vehicle according to the invention.

[0107] The runway preferably has two ends and the at least one energy absorbing system is arranged at the end of one or both ends of said aircraft runway.

[0108] The energy absorption system of the present invention can be part of an airport runway. Preferably, the energy absorption system covers an area having a length of 20 to 500 meters and a width of 20 to 100 meters.

[0109] Another aspect of the invention relates to a roadway comprising at least one energy absorbing system for stopping a transport device according to the invention.

[0110] The energy absorption system of the present invention can also be installed on roads and streets to stop or slow down transportation equipment. This can be useful, for example, to allow a truck or bus with broken brakes to leave the street or road at an emergency exit where the energy absorption system of the present invention is located. The energy absorption system of the present invention can also be used to protect certain areas from unauthorized vehicles.

[0111] The present invention is further illustrated by the following examples, which should not be construed as limiting the invention.

[0112] <Example> This example shows how the energy absorption system of the present invention (see FIG. 1) was manufactured.

[0113] Concrete Base 2

[0114] A concrete base 2 was applied onto a friable support 3 with a thickness of 20-200 mm, preferably 40-60 mm.

[0115] Primer System

[0116] The primer system was designed to seal the surface of the installed concrete base 2, eliminating any pinholes in subsequent layers of the system and preventing moisture penetration. However, the primer can also be used to coat a polyurethane layer. The primer was composed of 100% solids (no water) and was based on aromatic polyisocyanates and renewable resource polyols, namely castor oil. This has great environmental advantages. Although the primer is applied, it is designed to penetrate and seal the concrete, and does not provide a layer with a coating thickness.

[0117] Primer is 0.13 to 0.5 liters / m 2 Application rate (per unit area) of 0.2 to 0.25 liters / m 2 The primer was applied by brush or roller, high pressure airless spray or plural component spray.

[0118] The primer was based on an aromatic isocyanate component such as Huntsman Corporation's SUPRASEC 9584. This is an isocyanate component having an isocyanate content of 24.1%, a functionality of 2.67, and an equivalent weight of 174, with a viscosity of 45 cps @ 25°C.

[0119] The resin component was castor oil #1, castor bean (Ricinus Cumminus) seed oil, with a hydroxyl value of 60-100 and a viscosity of 200-600 cps@25°C (200-600 cps at 25°C).

[0120] The isocyanate and resin were mixed in a 1:1 volume ratio and applied to the substrate as described above.

[0121] Polyurethane layer 4

[0122] The spray foam system was a specially modified isocyanurate spray foam that was friable, highly flame retardant and resistant to burning. The foam system was based on a polyaromatic isocyanate and a resin blend of polyols, catalysts and water blown. The system was environmentally friendly as it used only water for expansion / blowing and did not use any added organic blowing agents.

[0123] The spray foam system was applied at ratios of 200:100 to 400:100 (isocyanate to resin / polyol), with the preferred treatment ratio being 200:100 to 250:100. The foam application thickness can be 15 to 40 mm, with the preferred application thickness being 20 to 30 mm.

[0124] The foam system can be applied to the primer system once the primer is tack-free (usually within 1.5 hours). The foam system is applied using a high pressure, heated, variable ratio plural component machine fitted with an impingement mix spray gun.

[0125] The system was based on the following formulation:

[0126] Isocyanate component: Polymeric MDI, 100 parts by weight, e.g. Huntsman's RUBINATE M

[0127] Resin Blend: PET-based polyol 70-90 parts by weight (hydroxyl value 250) Water 1.5~2.0 parts by weight Trischloropropyl phosphate (flame retardant) 11-15 parts by weight Silicone surfactant 1.3 to 1.8 parts by weight JEFFCAT TR 90 1.6~1.8 parts by weight JEFFACT ZF 10 0.5 to 0.7 parts by weight (catalyst, both manufactured by Huntsman) POLYCAT 34 0.6~0.8 parts by weight (Evonik catalyst) Potassium octoate 0.4 to 0.8 parts by weight (trimerization catalyst)

[0128] The spray foam system was processed at volume ratios of 200:100 to 400:100 (ISO to resin / polyol), with the desired processing volume ratio being 200:100 to 250:100.

[0129] Polyurea layer 5

[0130] Polyurea coating systems are aromatic polyureas with properties designed to provide good elasticity and strength even in low temperature exposure situations, including sub-freezing weather. Polyurea coating systems are multi-component systems based on aromatic prepolymer isocyanates and resin blends composed of amine-terminated resins. Polyurea coating systems are 100% solids systems that are very fast reactive and cure.

[0131] The polyurea system can be applied in thicknesses of 0.5 to 2.0 mm, with a preferred application thickness of 0.5 to 1.0 mm. The system is applied using a high pressure heated plural component machine fitted with an impingement mix spray gun.

[0132] The system was based on the following formulation:

[0133] Isocyanate component: SUPRASEC 2054 100 parts by weight (Huntsman, isocyanate content 15%, functionality 2.0)

[0134] Resin blend side: 50 to 70 parts by weight of JEFFAMINE D-2000 (manufactured by Huntsman, polyetheramine with a molecular weight of 2000) LONZA DETDA 17-20 parts by weight (Lonza, diethyltoluenediamine) UNILINK 4200 5-10 parts by weight (Dorf Ketal, methylenedianiline-based secondary amine). Aluminum trihydrate 5-10 parts by weight (Flame retardant from Clariant) Pigment colorant: 2 to 5 parts by weight Gel time: 5-10 seconds Tack free time: ~45 seconds

[0135] The system is processed in a high pressure, high temperature proportioning spray device at a 1:1 volume ratio.

[0136] Anti-slip Coat:

[0137] A topcoat can be applied over the polyurea system. This provides color stability and the ability to incorporate fine aggregate for slip resistance. The topcoat was based on an aliphatic polyurea system using polyaspartic acid ester resin. The topcoat application thickness was 0.25-1mm DFT, with a preferred application thickness of 0.4-0.6mm DFT. The topcoat can be applied by brush or roller, high pressure airless spray or plural component spray. The aggregate applied ranges from 0.2-0.5mm, with a preferred range of 0.3-0.4mm.

[0138] The system was based on the following formulation:

[0139] Isocyanate component: 100 parts by weight of HDI trimmer (DESMODUR 3900, N-100, or Tolonate HDT-LV, etc.)

[0140] Resin Blend Ingredients: DESMOPHEN NH-1420 55~65 parts by weight DESMOPHEN NH-1520 35-40 parts by weight (Bayer polyaspartic acid ester) Silquest A-1100 0.5 to 1.0 parts by weight (amino silane adhesion promoter manufactured by Momentive) BYK 354 1.7-2.2 parts by weight (defoamer - Byk Chemie) 1.4-1.7 parts by weight of Airex 900 (defoamer - Goldschmidt Chemical) Mix ratio by volume 1.0 ISO : 1.5 resin Gel time: 30-35 minutes Tack-free 1.0~1.5 hours

Claims

1. 1. A method of manufacturing an energy absorption system for shutting down a transportation device, comprising: a. applying concrete onto a friable support to form a concrete base; b. applying a first composition comprising at least one polyol, at least one catalyst, and at least one isocyanate onto the concrete base to form a polyurethane layer; c) applying a second composition comprising at least one polyamine and at least one isocyanate over said polyurethane layer to form a polyurea layer.

2. The method according to claim 1 , further comprising, after step a, applying a leveling composition onto the concrete base in step a1 to form a leveling layer.

3. 3. The method according to claim 1 or 2, further comprising applying on the concrete base after step a or after step a1, and optionally on the polyurethane layer after step b, a third composition comprising at least one polyol and at least one isocyanate, the third composition being substantially free of water.

4. 4. The method according to any one of claims 1 to 3, wherein a fourth composition comprising at least one polyamine and at least one defoamer, and at least one isocyanate is applied on top of said polyurea layer to obtain an anti-slip layer.

5. The method of any one of claims 1 to 4, wherein the concrete is substantially free of quartz.

6. The method according to any one of claims 1 to 5, wherein said at least one polyol of said first composition is selected from the group consisting of polyester polyols.

7. 7. The method according to any one of claims 1 to 6, wherein said at least one catalyst of said first composition is selected from the group consisting of 1,3,5-tris(dimethylaminopropyl)-1,3,5-hexahydrotriazine, N,N,N'-trimethyl-N'-hydroxyethyl-bisaminoethyl ether and potassium octoate.

8. A method according to any one of the preceding claims, wherein the first composition comprises 1 to 3 wt%, preferably 1.2 to 2 wt% of a surfactant, which is preferably a silicone surfactant.

9. 9. The method according to any one of claims 1 to 8, wherein the first composition comprises 1 to 5 wt.-%, preferably 1.2 to 3 wt.-%, more preferably 1.5 to 2 wt.-% of water, and / or 5 to 20 wt.-%, preferably 10 to 20 wt.-%, more preferably 11 to 15 wt.-% of a flame retardant.

10. 10. The method according to any one of the preceding claims, wherein the at least one isocyanate and the first composition are applied onto the concrete base to obtain a thickness of the polyurethane layer of 1 to 50 mm, preferably 1 to 40 mm, more preferably 1 to 30 mm, more preferably 1 to 20 mm, more preferably 1 to 15 mm, more preferably 5 to 10 mm.

11. 11. The method according to any one of the preceding claims, wherein said at least one isocyanate and said second composition are applied onto said polyurethane layer to obtain a thickness of said polyurea layer of 0.1 to 10 mm, preferably 0.2 to 5 mm, more preferably 0.5 to 3 mm, more preferably 0.5 to 2 mm, more preferably 0.5 to 1.2 mm, more preferably 0.5 to 1 mm.

12. 5. The method according to claim 4, wherein said at least one defoamer of said fourth composition is selected from the group consisting of silicone-based defoamers, preferably methylated silica and / or dimethyl silicone polymers.

13. 13. The method according to claim 4 or 12, wherein said fourth composition comprises 80% to 98% by weight, preferably 90% to 98% by weight, more preferably 95% to 98% by weight of said at least one polyamine, and / or 2% to 5% by weight, preferably 2% to 4% by weight of said at least one defoamer.

14. A method according to any one of claims 4, 12 and 13, wherein said at least one isocyanate and said fourth composition are applied onto said polyurea layer in a thickness of 0.1 to 2 mm, preferably 0.25 to 1 mm.

15. 3. The method of claim 2, wherein the leveling composition comprises at least one isocyanate and at least one polyamine and / or at least one polyol.

16. The method of claim 15 , wherein the leveling composition comprises quartz particles.

17. A method according to claim 16, wherein said quartz particles have an average size of 0.05 to 1 mm, preferably 0.05 to 0.75 mm, more preferably 0.05 to 0.5 mm, more preferably 0.1 to 0.5 mm.

18. The method according to any one of claims 15 to 17, wherein the levelling composition further comprises a floating agent, preferably pyrogenic silica.

19. 19. The method according to any one of claims 15 to 18, wherein said levelling composition comprises a mixture of said at least one polyol and said at least one polyamine in a ratio of 2:1 to 6:1, preferably 3:1 to 5:1, more preferably 3.5:1 to 4.5:

1.

20. 20. The method according to any one of claims 15 to 19, wherein said levelling composition comprises said at least one isocyanate and said at least one polyamine and / or at least one polyol in a ratio of from 3:1 to 7:1, preferably from 4:1 to 6:1, more preferably from 4.5:1 to 5.5:

1.

21. 18. The method according to claim 16 or 17, wherein said levelling composition comprises said at least one isocyanate and said quartz particles in a ratio of 3:1 to 1:1, preferably 2.5:1 to 1.5:1, more preferably 2:1 to 1.5:1, more preferably 1.8:1 to 1.7:

1.

22. 22. The method according to any one of claims 15 to 21, wherein the levelling composition comprises 0.5 to 1.2 wt.-%, preferably 0.6 to 1 wt.-%, more preferably 0.7 to 0.9 wt.-%, more preferably 0.8 to 0.9 wt.-% of a floating agent.

23. 23. A method according to any one of the preceding claims, wherein a first grid of cuts is formed in the concrete base, the cuts of the first grid starting on a surface of the concrete base opposite the friable support and extending towards the friable support, preferably having a depth less than a thickness of the concrete base.

24. 24. The method of any one of claims 1 to 23, wherein a second grid of cuts is formed, the cuts of the second grid originating on the surface of the polyurea layer opposite the polyurethane layer and extending through the polyurea layer, the polyurethane layer and the concrete base to the friable support.

25. 25. The method of claim 24, wherein the mesh size of the second grid is larger than the mesh size of the first grid.

26. 26. Method according to claim 24 or 25, wherein joint profiles are introduced inside at least some of the cuts of the first grid and / or inside at least some of the cuts of the second grid.

27. 27. The method of claim 26, wherein the joint profile comprises or consists solely of ethylene propylene diene monomer (EPDM) rubber.

28. An energy absorbing system for stopping a transport vehicle obtainable by the method according to any one of claims 1 to 27.

29. An energy absorbing system for arresting a transportation device comprising a concrete base positioned on a friable support and covered with at least one polyurethane layer and at least one polyurea layer on said at least one polyurethane layer.

30. 30. An aircraft runway or road comprising at least one energy absorbing system for stopping a transport device according to claim 28 or 29.

Citation Information

Patent Citations

  • Joint cutting method of concrete face

    JP1995091061A

  • vehicle restraint roadbed system

    JP2000511609A

  • Concrete-surface structure and its constructing method

    JP2005213842A

  • Jet resistant vehicle restraint block, restraint roadbed and method

    JP2005502801A

  • Tetraalkylammonium carboxylate salt as trimerization catalyst for spray foam application

    JP2008308689A